2007
DOI: 10.1002/ijc.23082
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of the urokinase receptor homologue, C4.4A, in invasive areas of human esophageal squamous cell carcinoma

Abstract: C4.4A is a glycolipid-anchored membrane protein with structural homology to the urokinase-type plasminogen activator receptor (uPAR). Although C4.4A was identified as a metastasis-associated protein little is known about its actual expression and possible function in malignant disease. In the present study, we have therefore analyzed the expression of C4.4A in 14 esophageal squamous cell carcinomas (ESCC). Normal squamous esophageal epithelium shows a strong cell surface associated C4.4A expression in the supr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
49
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 49 publications
13
49
0
Order By: Relevance
“…In the adjacent normal mucosa's squamous epithelium, there was strong LYPD3 staining in the cell membranes of differentiated cells, but no staining in the basal cell compartment (Figure 6g), which is consistent with previous staining data (Hansen et al, 2008). On the other hand, we found that LYPD3 is overexpressed in various stages of cancer development, including carcinoma in situ and carcinoma at more advanced stages.…”
Section: Lypd3 Is Overexpressed In Human Escc Tumorssupporting
confidence: 92%
See 2 more Smart Citations
“…In the adjacent normal mucosa's squamous epithelium, there was strong LYPD3 staining in the cell membranes of differentiated cells, but no staining in the basal cell compartment (Figure 6g), which is consistent with previous staining data (Hansen et al, 2008). On the other hand, we found that LYPD3 is overexpressed in various stages of cancer development, including carcinoma in situ and carcinoma at more advanced stages.…”
Section: Lypd3 Is Overexpressed In Human Escc Tumorssupporting
confidence: 92%
“…The exact biochemical functions of LYPD3 are unknown; however, it was shown to interact with the adhesion proteins laminin-1, laminin-5 and galectin-3, which might promote metastasis and matrix invasion (Paret et al, 2005). With regard to esophageal cancer, LYPD3 was proposed as a histological marker of invasion and metastasis for ESCC (Hansen et al, 2008). Our data extend the finding that LYPD3 is overexpressed in a high percentage of ESCCs, suggesting an important role in ESCC development.…”
Section: Deregulated Lkb1-crtc Signaling In Esophageal Cancersupporting
confidence: 78%
See 1 more Smart Citation
“…It was first described as a metastasis-associated cell surface protein in rat pancreatic tumor cells (2) and since then, has been associated with carcinogenesis in several different cancers (3)(4)(5). In cancer, C4.4A has been suggested to be involved specifically in tumor cell invasion via interaction with the extracellular matrix (2,6).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of C4.4A has also been detected in SCC of the head and neck (HNSCC) including esophageal SCC (ESCC) subtype (3,11). On the transcriptional level, approximately 50% of primary lung cancers and 75% of lung cancer metastases express C4.4A mRNA, whereas no expression has been detected in normal lung tissue (12,13).…”
Section: Introductionmentioning
confidence: 99%